Christian persecution, martyrdom, and orthodoxy - De Ste. Croix, G. E. M. (Geoffrey Ernest Maurice); Whitby, Michael; Streeter, Joseph (Oxford ; New York : Oxford University Press, 2006)
This volume brings together seven seminal papers by the great radical historian Geoffrey de Ste. Croix, who died in 2000, on early Christian topics, with an especial focus on persecution and martyrdom. Christian martyrdom is a topic which conjures up ready images of inhumane persecutors confronted by Christian heroes who perish for the instant but win the long-term battle for reputation. In five of these essays Ste. Croix scrutinizes the evidence to reveal the significant role ofChristian themselves, first as volunteer martyrs and later, after the triumph of Christianity in the early fourth ce
Aspects of the 'Great' persecution -- The Fourth Edict in the West and the date of the Council of Elvira -- Why were the early Christians persecuted? -- Voluntary martyrdom in the early church -- Heresy, schism, and persecution in the later Roman Empire -- The Council of Chalcedon / with additions by Michael Whitby -- Early Christian attitudes to property and slavery.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Persecution; Martyrdom -- Christianity; Church history -- Primitive and early church, ca. 30-600.; History; RELIGION -- History; Martelaarschap; Christenvervolgingen; Electronic books